Epigenetic regulation of transcription factors involved in NLRP3 inflammasome and NF-kB signaling pathways - Kaszycki, John; Kim, Minji (Frontiers in Immunology, 2025)
The NLRP3 inflammasome and NF-κB signaling pathways play crucial roles in orchestrating inflammation and immune defense.​ This review explores the intricate relationship between these pathways and epigenetic regulation, a field of growing importance in understanding immune responses. Epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNAs (ncRNAs), significantly influence the activity of genes involved in these pathways, thereby modulating inflammatory responses. The review provides a comprehensive overview of current research on how epigenetic mechanisms interact with and regulate the NLRP3 inflammasome and NF-κB signaling pathways. It delves into advanced epigenetic concepts such as RNA modifications and 3D genome organization, and their impact on immune regulation. Furthermore, the implications of these findings for developing novel therapeutic strategies targeting epigenetic regulators in inflammatory diseases are discussed. By synthesizing recent advancements in this rapidly evolving field, this review underscores the critical role of epigenetic regulation in immune signaling and highlights the potential for epigenetic-based therapies in treating a wide range of inflammatory conditions, including autoimmune disorders and cancer.